2006
DOI: 10.24841/fa.v14i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación De Hymenoptera Y Coleoptera (Insecta) en Diferentes Tipos De Vegetación De La Zona Reservada Allpahuayo – Mishana, Loreto, Perú

Abstract: Se analizó la composición de familias de los órdenes Hymenoptera y Coleoptera en cinco diferentes tipos de hábitat, basados en criterios geológicos y de vegetación, en la Zona Reservada Allpahuayo – Mishana, en el marco del curso “Uso de inventarios biológicos para revelar patrones de distribución geográfica de especies en la selva baja amazónica”, organizado por el proyecto Diversidad Biológica de la Amazonía Peruana, Perú Finlandia (BIODAMAZ), con el apoyo del Instituto de Investigaciones de la Amazonía Peru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Iannacone et al (2000), a mean diversity of 2.33. De la Cruz et al (2003) found high heterogeneity in the distribution according to plant formations present in the habitats sampled. Figure 4 shows the carbon sequestration in fruit species from plot 32, the association of the 12 years pijuayo trees (20 plants/ha) and 14 years old uvilla (Pouroma cecropiifolia Mart.)…”
Section: Determination Of Soil Arthropodsmentioning
confidence: 92%
“…Iannacone et al (2000), a mean diversity of 2.33. De la Cruz et al (2003) found high heterogeneity in the distribution according to plant formations present in the habitats sampled. Figure 4 shows the carbon sequestration in fruit species from plot 32, the association of the 12 years pijuayo trees (20 plants/ha) and 14 years old uvilla (Pouroma cecropiifolia Mart.)…”
Section: Determination Of Soil Arthropodsmentioning
confidence: 92%